Feasibility and efficacy of 8 week Glecaprevir/Pibrentasvir to treat incarcerated viraemic HCV patients: A case‐control study. (2nd December 2020) - Fiore, Vito; Ranieri, Roberto; Dell'Isola, Serena; Pontali, Emanuele; Barbarini, Giorgio; Prestileo, Tullio; Marri, Daniele; Starnini, Giulio; Sotgiu, Giovanni; Madeddu, Giordano; Babudieri, Sergio
Abstract: Inmates have higher HCV prevalence than general population, representing a fundamental step towards HCV eradication. Our aim was to compare 8‐week glecaprevir/pibrentasvir treatment in a case‐control study between incarcerated and free patients. Eleven Italian prisons and six outpatient clinics were involved. Patients were matched for sex, risk factors, METAVIR grade, HIV and HBV co‐infections. About 131 incarcerated (Group A) and 131 free patients (Group B) were included. Mean age was 43.0 ± 9.6 years and 42.8 ± 9.9 in Group A and B, respectively ( P  = .74). SVR rates were 96.2% and 99.2% in Group A and Group B respectively ( P  = .21). Five drop‐outs occurred in Group A, one in Group B. Incarceration, being PWIDs and OST were not associated with SVR reductions (CI 95%). In conclusion, imprisonment does not influence unplanned interruptions or SVR rates when receiving short‐term therapies. Short schedules with pangenotypic regimens could be a good approach to hard‐to‐reach populations, such as incarcerated patients.